Clinical features, investigations, and outcomes of pediatric limbic encephalitis: A multicenter study. Issue 1 (11th January 2022) - Sabanathan, Saraswathy; Abdel‐Mannan, Omar; Mankad, Kshitij; Siddiqui, Ata; Das, Krishna; Carr, Lucinda; Eltze, Christin; Eyre, Michael; Gadian, Jon; Hemingway, Cheryl; Kaliakatsos, Marios; Kneen, Rachel; et al.
Abstract: Objectives: To describe the clinical presentation, investigations, management, and disease course in pediatric autoimmune limbic encephalitis (LE). Methods: In this retrospective observational study, from the UK Childhood Neuroinflammatory Disease network, we identified children from six tertiary centers with LE <18 years old between 2008 and 2021. Clinical and paraclinical data were retrieved from medical records. Results: Twenty‐five children fulfilling LE criteria were identified, with median age of 11 years (IQR 8, 14) and median follow‐up of 24 months (IQR 18, 48). All children presented with seizures; 15/25 (60%) were admitted to intensive care. Neuroimaging demonstrated asymmetric mesial temporal changes in 8/25 (32%), and extra‐limbic changes with claustrum involvement in 9/25 (38%). None were positive for LGI1/CASPR2 antibodies (Abs), 2/25 were positive for serum anti‐NMDAR Abs, and 2/15 positive for anti‐Hu Abs; one died from relapsing neuroblastoma. Two children had serum and CSF anti‐GAD antibodies. Initial immune therapy included steroids in 23/25 (92%), intravenous immunoglobulin (IVIg) in 14/25 (56%), and plasma exchange in 7/25 (28%). The commonest second‐line treatment was rituximab in 15/25 (60%). Median duration of hospital admission was 21 days (IQR 11, 30). At last follow‐up, 13/25 (52%) had refractory seizures and 16/25 (64%) had memory impairment. Six children (24%) had modified Rankin Scale (mRS) scores ≥3. There was no significant difference in mRS, or long‐term cognitive and epilepsy outcomes in those who received rituximab versus those who did not. Interpretation: A diagnosis of autoimmune LE was associated with significant morbidity and adverse outcomes in this pediatric cohort.